Lateral Thoracotomy Implantation of Left Ventricular Assist Device: A Step Forward to Preserve Right Ventricular Function. Issue 1 (17th March 2021) - Attisani, Matteo; Frea, Simone; Pidello, Stefano; Barbero, Cristina; Lodo, Vittoria; Centofanti, Paolo; Cingolani, Marco M.; Aste, Andrea; Recchia, Elisa; Brenna, Dario; De Ferrari, Gaetano M.; Rinaldi, Mauro; et al.
Abstract : Supplemental Digital Content is available in the text.